Improved correlation of urinary cytology specimens using The Paris System in biopsy‐proven upper tract urothelial carcinomas. Issue 7 (21st June 2018) - McIntire, Patrick J.; Snow, Justin T.; Robinson, Brian D.; Rao, Rema A.; Goyal, Abha; Heymann, Jonas J.; Siddiqui, Momin T.
Abstract : BACKGROUND: Urine cytology specimens are essential for screening and monitoring high‐grade urothelial carcinomas. However, inconsistent reporting and equivocal diagnostic categories have remained a challenge. The Paris System for Reporting Urinary Cytology (TPS) was developed to provide clear cytomorphologic criteria for urine cytology specimens. Significant correlation between the surgical biopsy diagnosis (SD) and TPS diagnosis (PD) has been established in lower urothelial tract carcinomas, but to the authors' knowledge limited information is available regarding upper urinary tract carcinomas. METHODS: A total of 56 cytology specimens from 35 patients within 90 days of an SD of upper urinary tract carcinoma were included. Cytology was re‐reviewed and assigned a PD. The original diagnosis (OD) and PD were compared with the corresponding SD to determine which correlated best. RESULTS: The PD corresponded to the SD in 35 of 56 cases (63%), which was greater than that for the OD and SD, which were concordant in 19 of 56 cases (34%). Both the OD and PD were concordant in 18 of 56 cases (32%), and neither corresponded in 20 of 56 cases (36%). A total of 27 of 33 cases of high‐grade urothelial carcinoma/carcinoma in situ on SD (82%) were identified using the PD whereas only 15 cases (45%) were identified with the OD. The number of "atypical" diagnoses in the OD was reduced from 16 of 56 cases (29%) to 7 of 56 cases (13%) using the PD. Of the 14 of 56 "negative" OD (25%), only 4 remained after implementation of the PD. A diagnosis of low‐grade urothelial neoplasm was established in 6 of 20 cases (30%) with the PD compared with 3 of 20 cases with the OD (15%). CONCLUSIONS: The authors found that reclassification with TPS improved correlation with the SD compared with previous methodologies. Specifically, TPS increased the number of high‐grade urothelial carcinoma diagnoses and decreased the number of equivocal or "atypical" diagnoses. Cancer Cytopathol 2018. © 2018 American Cancer Society. Abstract : Reclassification with The Paris System for Reporting Urinary Cytology improves correlation with the surgical biopsy diagnosis compared with previous methodologies in patients with upper tract urinary carcinomas. Specifically, The Paris System for Reporting Urinary Cytology increased the number of high‐grade urothelial carcinoma diagnoses and decreased the number of equivocal or "atypical" diagnoses.